The Role of Magma Mixing in the Petrogenesis of Eocene Ultrapotassic Lavas, Western Yunnan, SW China. (29th December 2022) - Yang, Zongpeng; Hou, Tong; Wang, Dachuan; Marxer, Felix; Wang, Meng; Chebotarev, Dmitry; Zhang, Zhaochong; Zhang, Hongluo; Botcharnikov, Roman; Holtz, François
Abstract: Magma mixing is a widespread magmagenic process. However, its significance in the formation of ultrapotassic magmas has been largely overlooked so far as they are commonly thought to originate directly from the mantle and ascend rapidly through the crust. The Hezhong ultrapotassic lavas in Western Yunnan (SW China) are (basaltic) trachy-andesitic in composition. These rocks display porphyritic textures with olivine, clinopyroxene (Cpx), spinel, and phlogopite occurring as both phenocryst and glomerocryst. Disequilibrium textures and complex zonation of crystals are commonly observed. Specifically, based on the textural and compositional characteristics, olivines can be classified into three different populations: two populations are characterized by highly to moderately magnesian olivines with normal chemical core-rim zonation (Fo 94–86 to Fo 89–79 and Fo 91–89 to Fo 86–84, respectively). The third population lacks obvious crystal zonation, but individual crystals exhibit some compositional variety at lower Fo contents (Fo83–76 ). Similarly, four populations of Cpx and two populations of spinel phenocrysts are recognized in terms of texture and composition. Notably, Cpx with reverse zoning contains a 'green-core' surrounded by a colourless mantle and rim. Hence, based on the variations of mineral assemblage, types of inclusions, and chemical compositions, all phenocryst/glomerocryst minerals can be divided into three groups. Mineral Group I (MG I) consists of high Fo cores of olivine, cores of the zoned spinel, and phlogopite. MG II only includes the green cores of reversed zoned Cpx (green-core Cpx), and MG III is composed of micro phenocrysts without obvious zoning and rims of large phenocrysts. Comparing these mineral groups with relevant minerals occurring in typical temporally and spatially associated igneous rocks, we suggest that the MG I and II could have been derived from magmas with compositions resembling an olivine lamproite and a trachyte, respectively. The overall bulk-rock geochemical and isotopic features of Hezhong lavas also agree with a mixing process between these two endmembers. Hence, we infer that mixing between these two magmas played a key role in the petrogenesis of the ultrapotassic Hezhong lavas and that the MG III crystallized from the mixed magmas. Our study highlights the complex formation of ultrapotassic magmas inferring that caution must be taken when using bulk chemical magma compositions are to deduce source signatures.